Problematika Kepemimpinan Pendidikan Islam di Era Milenial - Harun, Harun (Ta’allum: Jurnal Pendidikan Islam, 2020)
Today we have entered the millennial era, which is happening so fast. Digital technology accompanies all human activities, in the current millennial, people are more preoccupied with technology such as using social media. Islamic leadership that adheres to Islamic principles will certainly make Islamic education able to overcome challenges and changes that occur so quickly. The type of research used was library research. The results of the study in the form of Islamic education leadership concept mean that not only includes influencing and facilitating what have been done but, including the ability used to ensure readiness to face challenges. The process must always be within Islamic values, namely the values ​​that bring up to shari’ah norms that was compatible with Islamic education. The problems of Islamic education leadership in millennial era was humans in the millennial era more concerned with the reason, leaving the spiritual, and decreasing millenial generation character. The solutions of Islamic education leadership problems in millenial era are the leaders have to have a character-based paradigm, able to develop Islamic education that responds to the development and demands of the times.